Peer relationships in middle childhood and adolescence - ŽUKAUSKIENĖ, R. (Psichologija, 1997)
Positive peer relationships and prosocial behaviour is known to emerge as major correlates of a positive status at each age. On the contrary, poor peer relationships are a vali d indicator of concurrent and subsequent. Adjustment problems. In this work, peer sociometric status (Coie, et al., 1983), Revised Class Play (Masten, et al., 1985) and teacher ratings of school achievement were obtained for 483 third-through seventh-grade children and adolescents, attending elementary and secondary schools. As we hypothesized, the correlations of positive status with the Sociability-Leadership factor and with school achievement were strongly positive. The correlations of positive status with the Aggressive-Disruptive factor were negative, and the strength of the relation varied with the age. The correlations of positive peer status with Sensitivity-lsolation factor increases with age. Our data provide support for the hypothesis about the age differences in process variables. School achievement was shown to play a more important role in peer acceptance in middle childhood than in adolescence. Prosocial behaviour was proved to be an important factor of high positive social status in middle childhood, while the aggressive behaviour was shown to influence the development of negative social status (and further adjustment problems) in adolescence. The relationships of negative status with isolated behaviour increased dramatically in adolescence, suggesting greater attention by peers to asocial and over-emotional behaviour.
Keywords: peer relationship; middle childhood; adolescence; positive status; aggressiveness; negative status